Profile of Cervical Cancer Management with Radiation and Chemoradiation Therapy at The Radiotherapy Installation of RSUP Dr. Mohammad Hoesin Palembang - Nurhidayat, Wahyudi; Andriani, Dini; Yuhedi, Lucky Taufika; Diyana, Wahyu (Perhimpunan Dokter Spesialis Onkologi Radiasi Indonesia (PORI), 2024)
Cervical cancer is a gynecologic malignancy that ranks as the second most common cancer affecting women, following breast cancer. Recommended therapy for locally advanced cervical cancer, according to PNPK (National Guidelines for Cancer Services) is chemoradiation or radiotherapy. The aim of this study is to present a comprehensive analysis of the management cervical cancer with chemoradiation and radiation therapy, which will allow for a comparison of outcomes, specifically the clinical tumor response and radiation-related side effects, in patients with locally advanced cervical cancer who received either radiation therapy alone or a combination of chemoradiation. This research is a retrospective observational study using our hospital database in 2022. SPSS was used for the data analysis. The study findings indicated a notable disparity between chemoradiation therapy and radiation alone in terms of treatment outcomes for patients with stage III cervical cancer, with a p-value of 0.011. The findings of this study indicate that the projected number of new cervical cancer cases at the RSMH Palembang Radiotherapy Installation in 2022 was 194 patients. The age ranged from 27 to 75 years, with an average age of 49.59 ± 9.29 years. A significant proportion, specifically 42%, of the domicile addresses of most patients originate from Palembang City and its surrounding areas. Stage III was the most advanced stage of patients, with a prevalence of 76%. The distribution of cervical cancer cell types was predominantly squamous cell carcinoma, accounting for approximately 80%, with adenocarcinoma comprising the remaining 20%. The overall efficacy of therapy for cervical cancer, regardless of the stage, was 63.5%.